Influence of thermal treatment conditions on porosity development and mechanical properties of activated carbon cloths from a novel nanofibre-made fabric - Ramos, M. E. (2009)
Activated carbon cloths (ACC) were prepared from Tencel®, a novel regenerated cellulose nanofibre fabric, by phosphoric acid activation in an inert atmosphere using different thermal treatment conditions. The effect of the final thermal treatment temperature (660-970°C) and temperature programme (temperature of isothermal step and heating rate) on yield, elemental composition and porosity development of the resulting ACC were examined. Nitrogen isotherms at -196ºC and carbon dioxide isotherms at 0ºC were determined for all the samples. Adsorption data were fitted to different models (BET, Dubinin-Radushkevich, αS) to evaluate textural parameters of the ACC. The samples were essentially microporous and presented good physical appearance. Higher treatment temperatures resulted in higher BET surface areas and total pore volumes, also leading to larger micropore widths. The ACC prepared at 963°C showed maximum BET surface area (1705 m2g-1) and total pore volume (0.67 cm3g-1). Results pointed out to a stronger dependence of surface area, total pore volume and microporosity development on the final treatment temperature than on the temperature programme.